Hydraulic mining operation on Nome Beach, September 23, 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: 1199. Nowell, 1904. On verso of image: Hydraulic mine on Nome Beach, Sept. 23, 1904 In June 1899, gold was found on the beaches of Nome, and by August, a number of men were prospecting the beaches. The news of the gold strike was carried to the States that winter and in early summer 1900 the rush was on. At the peak that summer, there were 30,000 people at Nome, but 16,000 left in 13 weeks. (pg. 694) Notes from Donald Orth, Dictionary of Alaska Place Names: Geological Survey Professional Paper 567 (Washington: United States Government Printing Office, 1967) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number